THE RELEVANCE OF THE NATIONAL ENTREPRENEURSHIP POLICY (NEP) 2030 IN MEETING THE NEEDS AND STRENGTHENING THE COUNTRY’S ENTREPRENEURIAL ECOSYSTEM: A SNAPSHOT - Irma Wani Othman; Saifulazry Mokhtar; Ismail Maidin; Mohd Maziz al-Hadi Moharam (International Journal of Accounting, Finance and Business, 2021)
This paper established a snapshot on the relevance of the National EntrepreneurshipPolicy (NEP) 2030 in meeting the needs and strengthening the country’s entrepreneurialecosystem. In this context, the focus is to identify various types of government developmentprogrammes in support of entrepreneurs, while creating a strong and competitive enterprise.Among the topics discussed were related to the significance of National EntrepreneurshipPolicy such as (a) cultural challenges and empower local entrepreneurs, (b) technologyintegration in entrepreneurship development, and (c) initiative for sustainable ecosystem. Thedirection of the discussion is on the country’s desire to realise superior entrepreneurship thusstrengthening the entrepreneurial development ecosystem. In fact, the emphasis of governmentprogramme initiatives is focused on measuring results, intensifying collaboration acrossministries, agencies and industries, enhancing the ability of entrepreneurs to be resilient,competitive and global in character and preparing entrepreneurs to be catalysts of trends andmarkets.